Efektivitas Pengendalian Internal, Ketaatan Aturan Akuntansi, Moralitas Individu, dan Kecenderungan Kecurangan Akuntansi - Paramitha, Made Ayu Rhetria Sashikirana; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 34 No 2 (2024), 2024)
The purpose of this research is to analyze the influence of the effectiveness of internal control, compliance with accounting rules, and individual morality on the tendency for accounting fraud. The data collection method was carried out by distributing questionnaires in the form of a Google Form. This research was conducted at the Denpasar City Public Works and Spatial Planning Department. The population in this study was the entire financial sub-section of the Public Works and Spatial Planning Department of Denpasar City, totaling 60 people. The data analysis technique used is multiple linear regression analysis. The results of this research state that internal control has a negative effect on the tendency for accounting fraud. Compliance with accounting rules has a negative effect on the tendency for accounting fraud. Individual morality has a negative effect on the tendency for accounting fraud.